ANALISIS DETERMINAN-DETERMINAN YANG MEMPENGARUHI KEMATIAN BAYI (STUDI KASUS DI KABUPATEN BANYUMAS) - Rahardjo, Setiyowati; Dardjito, Endo (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2009)
Infant Mortality Rate (IMR) is a common indicator used as economic development index, quality of life indicator and main component determining life expectancy rate of a society. Data from Banyumas Regency Health Office showed that infant mortality in 2006 was 5,65 per 1000 live birth and it increased in 2007 to 9,60 per 1000 live birth. The research aims to determinants analysis that influence infant mortality in Banyumas Regency. The research method used case control approach. The case was baby that died in year of 2007 to July 2008. The contol was baby those who live as the case?s neighbours. The case sample were taken from the data of Banyumas Regency Health Office as many as 44 newest infant mortality, while the control sample taken by using population based technique with the closest neighbours of the cases as the control source. The analysis used univariat, bivariat and multivariat. The result of the research states that determinant which correlated with infant mortality were close determinant that : birth weight (p = 0,004 dan OR = 4) and congenital disorder (p = 0,030 dan OR = 6,17). While the most dominant relevant factor was congenital disorder OR = 8,18 (95%CI 1,57-42,55) which means baby with congenital disorder risked 8,18 times to experience mortality compared to babies that who have congenital disorders. The result of the research suggested to make coordination with health service officer to give information and eduction about effects of congenital disorders in new born babies, and the mothers visit antenatal helath service regulary.